Psychological Contract Breach, Psychological Capital and Work Alienation: A Case of Tourism Agencies of Pakistan - Hassan, Naveed; Zafar, Muhammad Zeeshan (Minhaj International Journal of Economics and Organization Sciences, 2025)
The current study aims to investigate the impact of psychological contract breach on work alienation. The study also considers the intervening effect of psychological capital on the relationship. Theoretical framework developed based on assumption that mediation of psychological capital may reduce the negative effects of psychological contract breach. Data for current study collected from agents and employees of various tourist agencies working across Pakistan. Around 300 respondents participated in this study and selected through simple random sampling. Respondents contacted via social media. After a brief introduction of research and purpose of data collection, respondents participated voluntarily. Cross-sectional data then was analyzed using PLS-SEM via smart PLS 3.0 version. Current research is unique in its type as it determines the important cause of work alienation in organizations and provides solution for that. Results showed strong positive effect of psychological contract breach on work alienation. Psychological capital intervenes the said relationship. Research is helpful for both policy makers and private tourism agencies to take corrective actions to enhance tourism in Pakistan.